Fatwa Majelis Ulama Indonesia sebagai Solusi Permasalahan Umat Islam di Indonesia - Pelu, Ibnu Elmi Achmat Slamat; Tarantang, Jefry (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The Indonesian Ulema Council (MUI) has an important role in answering the increasingly complex problems of Muslims through fatwas. However, in the Indonesian legal system, fatwas are not considered a source of material law that has legal validity as a solution to the problems of Muslims in Indonesia. Therefore, this study aims to describe the position of fatwas in the legal system in Indonesia and the existence of the fatwas of the Indonesian Ulema Council in addressing the problems of the ummah. This research is a normative legal research using three types of approaches consisting of a statutory approach, a historical approach, and a conceptual approach. The results of this study concluded that: firstly, the position of fatwas in the construction of Islamic law has a high position. Fatwas are seen as a solution that can break the ice in legal development that is not accommodated by the texts of the Quran. So, substantively and sociologically, fatwas have a strong and binding position in Islamic law. Secondly, the existence of the fatwa of the Indonesian Ulema Council in responding to the problems of the Ummah can be seen in two aspects. The first aspect, fatwas in the perspective of Islamic legal authority are binding sociologically in substance. This is because fatwas are explanations and interpreters of the texts of the Quran regarding Islamic law. The second aspect, fatwas from the perspective of the hierarchy of laws and regulations, legally and formally, do not have any position in the ranking of legal norms. However, it is constitutionally guaranteed through Article 29 of the 1945 Constitution that guarantees the realization of the fulfillment of all Islamic law for Muslims in Indonesia.